Forbidden games = Jeux interdits - Smith.L.J; Boyer, Francois; Clement, Rene.; Poujouly, Georges; Fossey, Brigitte; Badie, Laurence ([New York : Video Dimensions, 1988)
Anti-war film about a family who takes in a little girl who was orphaned during World War II. The youngest son and the little girl become great friends and learn to rely on each other.
French dialogue, English subtitles.
Based on a story by Francois Boyer.
Originally released as motion picture in 1952.
Keywords: World War, 1939-1945 -- France; Children and war; War films; Motion pictures, French; Motion pictures -- France